Nur Al-Din Mahmud Zanki’s (1146-1174 CE) Perspective On Bayt Al-Maqdis: A Historical Overview - Mohd Bakri, Mohamad Fikri; Shu’aibu (Al-Muqaddimah: Online Journal of Islamic History and Civilization, 2024)
Since the Crusaders’ takeover of Bayt al-Maqdis in 1099 CE, several Muslim leaders made efforts to reclaim the holy city. One of them was Nur al-Din Mahmud Zanki of the sixth century AH who gave special consideration to the liberation of Bayt al-Maqdis. He initially attempted to unify the regions in Syria and move the mission towards the liberation of Bayt al-Maqdis. However, some Western writers evaluate Nur al-Din’s efforts as purely political with the propaganda of Jihad to liberate Bayt al-Maqdis. This claim is outrightly different from the various sources of early Muslim historians who praised Nur al-Din’s efforts. This article discusses the position of Bayt al-Maqdis and the efforts made by Muslim leaders, especially Nur Al-Din throughout his reign under the Zengid Dynasty to liberate Bayt al-Maqdis. This is historical research with a qualitative approach. The primary sources analysed using inductive methods to achieve the desired objectives. Therefore, Nur Al-Din was a leader with a clear vision to recapture Bayt al-Maqdis against the Orientalist allegations of political and military missions.